Structure and Magnetization of Strontium Hexaferrite (SrFe12O19) Films Prepared by Pulsed Laser Deposition - Khojaste khoo, M.; Kameli, P. (Frontiers in Materials, 2021)
M-type strontium hexaferrite (SrM) thin films show excellent magnetic properties and uniaxial magnetic anisotropy. We have systematically investigated the magnetism of SrM films prepared by pulsed-laser deposition on different substrates (Al2O3 (11̅02), SrTiO3 (100), ZnO (0001), LiNbO3 (0001)) at vacuum(10-6mbar) and substrate temperature of 800°C. Prepared films were annealed in air at a temperature of 1000 °C for two h. This investigation determined the effect of annealing and different substrates on the films' morphology, strain, and hysteresis loops. The prepared films were characterized using x-ray diffraction, Raman spectroscopy, scanning electron microscopy, and superconducting quantum interference device(SQUID) magnetometer. X-ray diffraction analysis confirms the c-oriented growth along the out-of-plane. We found that annealing causes crystallization of films and a significant increase in coercivity. The highest coercivity of ~11KOe was measured for the film on Al2O3 (11̅02) substrate.